Recent Developments in the Application of Artificial Intelligence in the Diagnosis and Treatment of Osteoarthritis - GUO Tianci, CHEN Jixin, YU Weijie, LIU Aifeng (Zhongguo quanke yixue, 2023)
Osteoarthritis (OA) is a degenerative disease frequently encountered clinically, which can lead to loss of joint function in the late stage and is associated with a high disability rate. There is still no available cure for OA. Therefore, early diagnosis and precise treatment are the key to improving the therapeutic effect. Being an interdisciplinary research focus, artificial intelligence (AI) has been increasingly used in the diagnosis and treatment of OA recently, as it improves the diagnostic accuracy as well as clinical treatment and prognosis of OA. We summarized and systematically reviewed the literature on the application of AI in the diagnosis and treatment of OA, in which the application potential in assisting imaging diagnosis, surgical treatment, progression prediction and postoperative rehabilitation of OA was indicated, yet some limitations including non-standardized data collection and unstable algorithmic system were also identified. In the future, it is expected to establish a standardized clinical sample database and continuously optimize the algorithmic model, so as to better incorporate AI technologies in the diagnosis and treatment process of OA.